(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This objective of the research was to find and analyse the influence of financial and non-financial information on investment decisions of individual investors in North Sumatra with the intention of mediating and recommendations of financial advisors as moderator. This research was causality, with primary data. Data collection technique was to use questionnaires and documentation. The data analysis technique was to use statistical analysis based on partial least square (PLS). The results found that financial and non-financial information positively affected investor’s intentions and investment decisions. Investor’s intention was to mediate the influence of financial and non-financial information on investment decisions, while the recommendations of financial advisors did not moderate the influence of financial and non-financial information on investor’s intentions.